2021
DOI: 10.3390/ijms221910792
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Peritoneal Macrophages in Endometriosis

Abstract: Endometriosis is an estrogen-dependent gynecological disorder, defined as the growth of endometrial stromal cells and glands at extrauterine sites. Endometriotic lesions are more frequently located into the abdominal cavity, although they can also be implanted in distant places. Among its etiological factors, the presence of immune dysregulation occupies a prominent place, pointing out the beneficial and harmful outcomes of macrophages in the pathogenesis of this disease. Macrophages are tissue-resident cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 137 publications
(210 reference statements)
2
36
0
Order By: Relevance
“…Macrophages, deriving from monocytes, and neutrophil granulocytes, play a significant role in the development of inflammation and the immune response in the peritoneal environment; therefore, examining these cells from peripheral blood seems to be important [ 26 , 27 ]. It was also demonstrated that macrophages produce a significantly increased amount of proinflammatory cytokines, and there are data about defects in the phagocyte function [ 28 , 29 ]. Macrophages, natural killer cells and dendritic cells are present in peritoneal fluid with altered immunological function, which may be responsible for the residues of invaded menstrual debris [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Macrophages, deriving from monocytes, and neutrophil granulocytes, play a significant role in the development of inflammation and the immune response in the peritoneal environment; therefore, examining these cells from peripheral blood seems to be important [ 26 , 27 ]. It was also demonstrated that macrophages produce a significantly increased amount of proinflammatory cytokines, and there are data about defects in the phagocyte function [ 28 , 29 ]. Macrophages, natural killer cells and dendritic cells are present in peritoneal fluid with altered immunological function, which may be responsible for the residues of invaded menstrual debris [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have found that the inflammatory response, peripheral nerve sensitization, and pelvic adhesion are involved in the generation of pelvic pain in EMs. They interact with each other, directly or indirectly to stimulate nerve endings or mediate the sensitivity of nerve endings, thus inducing pain [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Physiologically, tissue resident macrophages display a continuous flux of phenotypes and differentiation or polarization profiles, which allow them to constantly adapt to their environment. The alteration of this homeostatic macrophage balance has been related with several diseases [ 8 , 10 , 33 ]. Different in vitro methods can be found in the literature to obtain a concrete polarization phenotype of macrophages from blood monocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed a complete blockade of IL-10 production after 24 h of exposure with free SFN and SFN-loaded in broccoli membrane vesicles. This effect represents a new opportunity for clinical application for diseases in which the activity of M2 macrophages must be controlled, such as endometriosis where M2 macrophages support the growth of endometrial lesions contributing to the disease progression [ 8 ], or cancer where tumor-associate macrophages, similar in phenotype to M2 macrophages, promote tumor growth and metastasis and are associated with poor prognosis of tumors [ 5 ], among others.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation